Advances in Proteomics Allow Insights Into Neuronal Proteomes - Fingleton, Erin; Li, Yan; Roche, Katherine W. (Frontiers in Molecular Neuroscience, 2021)
Protein-protein interaction networks and signaling complexes are essential for normal brain function and are often dysregulated in neurological disorders. Nevertheless, unraveling neuron- and synapse-specific proteins interaction networks has remained a technical challenge. New techniques, however, have allowed for high-resolution and high-throughput analysis, enabling quantification and characterization of various neuronal protein populations. Over the last decade, mass spectrometry (MS) has surfaced as the primary method for analyzing multiple protein samples in tandem, allowing for the precise quantification of proteomic data. Moreover, the development of sophisticated protein-labeling techniques has given MS a high temporal and spatial resolution, facilitating the analysis of various neuronal substructures, cell types, and subcellular compartments. Recent studies have leveraged these novel techniques to reveal the proteomic underpinnings of well-characterized neuronal processes, such as axon guidance, long term potentiation, and homeostatic plasticity. Translational MS studies have furthermore facilitated a better understanding of complex neurological disorders, such as Alzheimer’s, Schizophrenia, and Autism. Proteomic investigation of these diseases has not only given researchers new insight into disease mechanisms but have also been used to validate disease models and identify new targets for research